Flavonoid-rich fruit and vegetables improve microvascular reactivity and inflammatory status in men at risk of cardiovascular disease—FLAVURS: a randomized controlled trial. Issue 3 (22nd January 2014) - Macready, Anna L; George, Trevor W; Chong, Mary F; Alimbetov, Dauren S; Jin, Yannan; Vidal, Alberto; Spencer, Jeremy PE; Kennedy, Orla B; Tuohy, Kieran M; Minihane, Anne-Marie; Gordon, Michael H; Lovegrove, Julie A; et al.
ABSTRACT: Background: Observed associations between increased fruit and vegetable (F&V) consumption, particularly those F&Vs that are rich in flavonoids, and vascular health improvements require confirmation in adequately powered randomized controlled trials. Objective: This study was designed to measure the dose-response relation between high-flavonoid (HF), low-flavonoid (LF), and habitual F&V intakes and vascular function and other cardiovascular disease (CVD) risk indicators. Design: A single-blind, dose-dependent, parallel randomized controlled dietary intervention study was conducted. Male and female low-F&V consumers who had a ≥1.5-fold increased risk of CVD ( n = 174) were randomly assigned to receive an HF F&V, an LF F&V, or a habitual diet, with HF and LF F&V amounts sequentially increasing by 2, 4, and 6 (+2, +4, and +6) portions/d every 6 wk over habitual intakes. Microvascular reactivity (laser Doppler imaging with iontophoresis), arterial stiffness [pulse wave velocity, pulse wave analysis (PWA)], 24-h ambulatory blood pressure, and biomarkers of nitric oxide (NO), vascular function, and inflammation were determined at baseline and at 6, 12, and 18 wk. Results: In men, the HF F&V diet increased endothelium-dependent microvascular reactivity ( P = 0.017) with +2 portions/d (at 6 wk) and reduced C-reactive protein ( P = 0.001), E-selectin ( P = 0.0005), and vascular cell adhesion molecule ( P = 0.0468) with +4 portions/d (at 12 wk). HF F&Vs increased plasma NO ( P = 0.0243) with +4 portions/d (at 12 wk) in the group as a whole. An increase in F&Vs, regardless of flavonoid content in the groups as a whole, mitigated increases in vascular stiffness measured by PWA ( P = 0.0065) and reductions in NO ( P = 0.0299) in the control group. Conclusion: These data support recommendations to increase F&V intake to ≥6 portions daily, with additional benefit from F&Vs that are rich in flavonoids, particularly in men with an increased risk of CVD. This trial was registered at www.controlled-trials.com as ISRCTN47748735.